Th1- and Th17-Related Cytokines in Venous and Arterial Blood of Sclerodermic Patients with and without Digital Ulcers. (7th October 2019) - Nicola, S.; Fornero, M.; Fusaro, E.; Peroni, C.; Priora, M.; Rolla, G.; Bucca, C.; Brussino, L.
Abstract : The earliest clinical manifestation of SSc is usually Raynaud's phenomenon, a small-arteries vasospasm driven by vascular tone dysregulation and microcirculatory abnormalities, resulting in digital ulcers (DU) in up to 50% of patients. Many cytokines as well as growth factors have been shown to play a role in promoting vascular smooth muscle cell proliferation and fibroblast activation, leading to ischemic damage as well as skin fibrosis. We aim to investigate a possible difference in venous and arterial blood levels of many cytokines (Th1- and Th17-related), GM-CSF, and endothelin-1 (ET1) in patients with and without DU. In the same patients, the correlations between capillary damage, evaluated by nailfold videocapillaroscopy (NVC), extension of skin fibrosis, calculated by modified Rodnan skin score (mRSS), and cytokines, ET-1, and GM-CSF levels were also measured. Patients with DU showed venous levels of IL-1 β (p = 0.024 ), IL-6 (p = 0.012 ), IL-22(p = 0.006 ), and TGF- β (p = 0.046 ) significantly higher compared to arterial levels and arterial levels of GM-CSF and TNF-alpha significantly higher compared to venous levels (p < 0.001 ). NVC abnormalities were correlated with arterial TNFa and venous IL22, IL23, and IL17 levels and negatively correlated with venous ET-1 levels, whereas mRSS showed a negative correlation with IL-21( ρ = −0.427, p = 0.050 ). The increased Th17-cytokine levels in venous compared to arterial blood of patients with DU suggest local cytokine production on ulcer site. The higher TNFa and GM-CSF levels in arterial blood of DU patients support the attempt to mitigate the hypoxic damage, and the correlation between Th17-cytokines, mRSS, NVC, and ET1 agrees with the potent profibrotic stimulus at the onset of the disease, which decreases as the SSc progresses.